2017
DOI: 10.1126/science.aak9589
|View full text |Cite
|
Sign up to set email alerts
|

Vectorial representation of spatial goals in the hippocampus of bats

Abstract: To navigate, animals need to represent not only their own position and orientation, but also the location of their goal. Neural representations of an animal's own position and orientation have been extensively studied. However, it is unknown how navigational goals are encoded in the brain. We recorded from hippocampal CA1 neurons of bats flying in complex trajectories toward a spatial goal. We discovered a subpopulation of neurons with angular tuning to the goal direction. Many of these neurons were tuned to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
279
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(317 citation statements)
references
References 29 publications
(25 reference statements)
24
279
5
1
Order By: Relevance
“…As Mouritsen et al [2016] point out, there are obvious similarities at the conceptual level between the maps and compasses that are the basis of most theorizing about bird navigation and the place cells, grid cells, and head direction cells dedicated to processing map-like representations of space and bearing in rodents. In bats, the occurrence of hippocampal cells that resemble the place cells of rodents but with additional properties adapted to flight in 3D space and the discovery of other spatially responsive cells in the bat hippocampus [Sarel et al, 2017] encourage this latter view that there probably are common neural principles for representing space in the hippocampus of birds and mammals.…”
Section: Final Commentsmentioning
confidence: 99%
See 2 more Smart Citations
“…As Mouritsen et al [2016] point out, there are obvious similarities at the conceptual level between the maps and compasses that are the basis of most theorizing about bird navigation and the place cells, grid cells, and head direction cells dedicated to processing map-like representations of space and bearing in rodents. In bats, the occurrence of hippocampal cells that resemble the place cells of rodents but with additional properties adapted to flight in 3D space and the discovery of other spatially responsive cells in the bat hippocampus [Sarel et al, 2017] encourage this latter view that there probably are common neural principles for representing space in the hippocampus of birds and mammals.…”
Section: Final Commentsmentioning
confidence: 99%
“…Other cells in CA1 of the bat hippocampus are tuned to the direction and distance toward a goal. As the bat flies, and the vector between the moving bat and its goal changes, different goal direction cells become active or fall silent [Sarel et al, 2017]. Rats spatial neurons, in contrast, appear to reduce the problem of navigating in 3D space to navigation in a 2D plane, even when that plane is inclined, vertical, or inverted [Jeffrey et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarel et al 217 recorded from the CA1 region of flying bats, which have hippocampal-parahippocampal spatial representations similar to that of rodents [218][219][220] . The investigators identified a set of cells that responded as a function of the animal's orientation toward a salient goal positioned centrally in the environment.…”
Section: Co M M E N Ta Rymentioning
confidence: 99%
“…specifically encode the distance and direction to a goal (Sarel et al, 2017). One interpretation of these data is that the hippocampus may form two overlapping maps: one representing actual spatial relationships and the other representing the relative relationship between the animal and one or more salient locations.…”
Section: Sarel Et Al Recently Reported That Hippocampal Neurons In Bmentioning
confidence: 99%